Metabolic Associated Fatty Liver Disease Is Associated With an Increased Risk of Severe COVID-19: A Systematic Review With Meta-Analysis - Hegyi, Péter Jenő; Váncsa, Szilárd; Ocskay, Klementina; Dembrovszky, Fanni; Kiss, Szabolcs; Farkas, Nelli; Erőss, Bálint; Szakács, Zsolt; Hegyi, Péter; Pár, Gabriella (Frontiers in Medicine, 2021)
Background: The most common pre-existing liver disease, the metabolic dysfunction-associated fatty liver disease (MAFLD) formerly named as non-alcoholic fatty liver disease (NAFLD), may have a negative impact on the severity of COVID-19. This meta-analysis aimed to evaluate if MAFLD or NAFLD are associated with a more severe disease course of COVID-19. Methods: A systematic search was performed in five databases for studies comparing severity, the rate of intensive care unit (ICU) admission, and mortality of COVID-19 patients with and without MAFLD or NAFLD. In meta-analysis, pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Results: Altogether, we included nine studies in our quantitative and qualitative synthesis. MAFLD was associated with an increased risk of severe COVID-19 compared to the non-MAFLD group (28 vs 13%, respectively; OR=2.61, CI: 1.75–3.91). Similarly, in the NAFLD vs non-NAFLD comparison, NAFLD proved to be a risk factor as well (36 vs 12%, respectively; OR=5.22, CI: 1.94–14.03). On the other hand, NAFLD was not associated with an increased risk of ICU admission (24 vs 7%, respectively; OR=2.29, CI: 0.79–6.63). We were unable to perform a meta-analysis to investigate the association of MAFLD with the rate of ICU admission and with mortality. Conclusion: In conclusion, patients with MAFLD and NAFLD showed a more severe clinical picture in COVID-19. Our results support the importance of close monitoring of COVID-19 patients with MAFLD. Further research is needed to explore the cause of increased severity of COVID-19 in MAFLD.